Posterior hemivertebra resection without internal fixation in the treatment of congenital scoliosis in very young children - Xia, Bing; Wang, Hongqian; Dong, Yingmei; Liu, Fuyun; Wang, Wenjing; Hu, Weiming; Wang, Feipeng; Ma, Fengqun; Wang, Kai (Frontiers in Surgery, 2023)
Objective To retrospectively analyze the feasibility and efficacy of posterior hemivertebra resection without internal fixation in the treatment of congenital scoliosis in very young children. Methods Sixteen cases of very young children with congenital scoliosis treated at our hospital from April 2000 to July 2019 were collected, including 8 cases of each sex, all of whom had type I/III congenital scoliosis and were operated on at a median (interquartile range) of 9.00 (7.75) months (range, 0.5–48 months) of age. All cases underwent posterior hemivertebra resection without internal fixation and wore orthopedic braces or plaster undershirts for more than six months after surgery, with a mean follow-up of 94.31 ± 65.63 months (range, 36–222 months). Results Coronal plane: the preoperative Cobb angle for the segmental curve was 39.50 ± 9.70° compared to postoperative (19.19 ± 8.56°) and last follow-up (14.94 ± 12.11°) (both P < 0.01); the preoperative Cobb angle for the main curve was 34.19 ± 14.34° compared to postoperative (17.00 ± 11.70°) and last follow-up (17.56 ± 16.31°) (both P < 0.01); the preoperative Cobb angle of the proximal compensated curve was 14.88 ± 9.62° compared to postoperative (7.88 ± 4.66°) and last follow-up (8.38 ± 8.36°) (both P < 0.05); and the preoperative Cobb angle of the distal compensated curve was 13.50° (10.50°) (range, 4°–30°) compared with postoperative 4.50° (9.25°) (range, −3° to 25°) and final follow-up 5.50° (9.50°) (range, −3° to 33°) (both P < 0.01). Sagittal plane: the difference in the preoperative Cobb angle was 10.00° (14.00°) (range, −31° to 41°) for segmental kyphosis compared to postoperative 14.00° (24.50°) (range, −6° to 46°) and last follow-up 17.00° (22.55°) (range, −40° to 56°), and these were not statistically significant (both P > 0.05). There was a tendency for the thoracolumbar kyphosis to worsen and the lumbosacral kyphosis to improve during the follow-up period. Conclusion Posterior hemivertebra resection without internal fixation is a feasible treatment for type I/III congenital scoliosis in very young children, but the correction of the sagittal deformity of the thoracolumbar spine is not satisfactory, and postoperative external fixation may require further improvement.